Restless stars - Peckham, Caroline; Valenti, Susanne (Peckham, Caroline. Zodiac Academy, 2024)
We are all and nothing now, our fate weighed on the scales of the stars and counterbalanced by the forces that oppose us. The shadow of the false king spreads as thick as oil across the kingdom we were born to rule, and none remain untouched by its darkness. Our crowns lay within reach if only we can claim them. All souls are at risk now and when the final battle dawns, a new regime will rise. The time for the true reckoning is upon us and we have proven ourselves as savage as our father, as brutal as our mother, and as wild as the Elements which roar through our veins. We can only hope it is enough. When the last sword strikes the final death in this game of fate and fortune, only one side will be victorious. The Starfall Legion charges at first light. And our destiny rides upon our shoulders as we rush into the end. All hail the True Queens. May our rule last longer than this night.